Islands of Mind and Matter: Challenging Dualism in J. G. Ballard's 'The Terminal Beach' and The Chinese Room's Dear Esther. Issue 3 (December 2018) - Caracciolo, Marco
Abstract : Ideas enter our mind, a realisation can dawn on us, and we should let bad news sink in . This article argues that experimental narrative can destabilise this widespread tendency to describe mental processes through spatial metaphors. My case studies are J. G. Ballard's short story 'The Terminal Beach' (1964) and Dear Esther (2012), an arthouse video game developed by The Chinese Room. These narratives develop and literalise metaphors for mind by foregrounding the continuity between the physical space of the setting (an island) and the protagonists' existential predicament. Going beyond a dualistic reading of the 'mind as space' metaphor, these texts construct spaces that are more than a symbol for the characters' mental processes: narrative space is causally linked to mind in neurophysiological terms (in Ballard's short story), or extends the protagonist's emotional meaning-making (in Dear Esther ). This set-up is unsettling, I contend, because it raises deep questions about the relationship between subjective experience and material realities. By exploring these narratives and their ramifications, the article seeks to open a conversation between the cognitive humanities and the 'nonhuman turn' in contemporary literary studies.